Jasa penyerbukan serangga pengunjung bunga pada pertanaman stroberi di Ciwidey, Bandung - Masyitah, Siti; Rauf, Aunu; Maryana, Nina; Kahono, Sih (Jurnal Entomologi Indonesia, 2019)
Strawberry (Fragaria x ananassa Duch) is a horticultural crop whose pollination partly depends on insects. Study was conducted in a strawberry field in Ciwidey-Bandung, with the objective to assess the contribution of flower-visiting insects to strawberry pollination. In this study, the contribution was assessed by pollinators abundance, duration of visits to flower, and pollination efficiency i.e. number of developed achenes, fruit weight and size, and ripening time. The study recorded four most frequent strawberry flower visiting insects which were two hoverfly species:  Episyrphus balteatus (Deg.) (47.3%) and Melanostoma sp. (33.8%); and two bee species: Lasioglossum sp. (7.0%) and Asian honey bee Apis cerana Fabricius (5.3%). Duration of visit per flower by the hoverflies was 7.75–10,00 minutes and by the bees was 0.25–0.79 minutes. Fruits developed from flowers that had received a single visit by each insect species had more number of developed achenes (1.6-1.8 times), higher fruit weight (1.8–2.3 times), bigger fruit size (1.2–1.3 times), and shorter ripening time (1–3 days), compared to those fruits developed from flowers not visited by the insect. The presence of bees and hoverflies play an important contribution to strawberry pollination in Ciwidey. Our findings have implications for increasing strawberry yield through management of insect pollinators.